Penerapan Teknik Reinforcement dalam Upaya Meningkatkan Komunikasi Efektif pada Layanan Konseling Kelompok - Sutrisno, Tri (Universitas Islam Negeri Madura, 2022)
The research was conducted using a counseling guidance action research approach (PTBK) with the research subject of class XI Pharmacy students of SMK Kesehatan Mulia Husada Sumenep. The research was carried out in three cycles, using instruments in the form of RPBK, student activity observation sheets, BK teacher activity observation sheets and student response questionnaires to the application of reinforcement techniques. The conclusions of this research are (1) through the cycle of counseling guidance actions can be found effective steps for applying reinforcement techniques in an effort to increase effective communication in group counseling. (2) Through the cycle of counseling guidance actions, the application of reinforcement techniques has been proven to improve effective communication in group counseling services. Based on the conclusions of this study, it is recommended: (1) The main purpose of using reinforcement techniques is to develop active opinion and work together. Therefore BK teachers as providers of counseling services must prioritize processes that support the creation of a communicative, interactive and group work atmosphere. (2) BK teachers still need to continuously prove the application of reinforcement techniques in accordance with all types of counseling guidance services and client/student characteristics.